The Effect of Ownership Concentration on Financial Disclosure Practices (gjstudies, 2025)
This research investigates the nuanced and often paradoxical relationship between concentrated ownership structures and the quality of financial disclosurepractices in publicly traded corporations. Moving beyond the traditional agencytheory framework that predominantly views concentrated ownership as a monitoring mechanism that enhances transparency, we propose and test a novel, multidimensional model. This model posits that the effect of ownership concentration isnot linear but is instead contingent upon the identity of the dominant shareholder(e.g., founding family, institutional investor, state entity), the strength of countervailing governance institutions, and the strategic objectives related to proprietaryinformation costs. Utilizing a hand-collected, longitudinal dataset of 1,200 firmsacross 40 countries over a ten-year period, we employ a machine learning-basedtextual analysis of annual reports and regulatory filings to construct a granular,continuous disclosure quality index. This index captures not only the quantitybut the strategic obfuscation, readability, and forward-looking content of disclosures. Our findings reveal a significant bifurcation: while ownership concentrationby long-term institutional investors is associated with enhanced, clearer disclosure,concentration in the hands of founding families or state-owned entities correlateswith strategically selective transparency—increased disclosure on non-proprietarymatters but deliberate opacity in areas critical to competitive advantage or political scrutiny. Furthermore, we identify a critical moderating role of national-levelsecurities regulation enforcement; strong enforcement mitigates the negative effectsof certain ownership types, while weak enforcement exacerbates them. The studycontributes original insights by reframing disclosure not as a uniform good but asa strategic tool whose deployment is shaped by the intersection of ownership identity, institutional context, and competitive landscape, offering a more sophisticatedunderstanding of corporate transparency determinants.